Chiral catalysts utilized in the nucleophilic addition of dialkyl-zinc reagents to carbonyl compounds - Çetin, Adnan (Bentham Science Publ Ltd, 2020)
The aim of this review is an overview of diverse dialkyl zinc pro-chiral aldehydes addition reactions. One way of conducting asymmetric reactions is through the use of chiral catalyst. Therefore, new chiral ligands have attracted considerable attention in organic chemistry. Carbon-carbon bond formation reactions are an active research topic. The addition of dialkyl zinc to pro-chiral aldehydes is one of these popular reactions. Also, the chiral amino alcohols are important substrates for drug synthesis. These chiral ligands can be prepared by a simple synthetic way from easily accessible starting materials. This article reviews current catalyst reactions with the addition of dialkyl zinc to carbonyl compounds.
Keywords: Asymmetric synthesis; Amino alcohol; Binols; Chirality; Chiral recognition; Ee